GP220 Priority for complementary feeding start counseling and related nutritional recommendations from pediatricians during the first year of life. (June 2019) - Brambilla, Paolo; Picca, Marina; Bottaro, Gaetano; Giussani, Marco; Buzzetti, Roberto; Becherucci, Paolo
Abstract : Introduction and aim: An early education to avoid an excessive protein and salt consumption is now considered crucial for obesity and hypertension prevention. Complementary feeding (CF) practices are debated among Pediatricians, first of all about which criterion should be considered between nutritional needs (NN) or developmental readiness (DR) for CF start. The aim of the present study was to analyze if timing of CF, modalities, and nutritional advices during the first year of life were related with the criterion considered for CF start among Pediatricians. Methods: An online Survey was conducted in march 2018 among Family Pediatricians in Italy investigating the criterion chosen for CF start, timing, method of feeding and specific dietary practices. A Good Nutritional Practice (GNP) was acknowledged to those Pediatricians who declared to give advices for meat quantity and salt consumption during the first year of life respect to those who declared to demand any decision to parents. Results: Participation rate was 43.3% (350 of 808) among active members of the Italian Society of Primary Care Pediatricians (SICuPP), 213 of them (60.9%) choose DR and 137 (39.1%) NN as CF starting criterion. About 75% declared to counsel CF start between 5 and 6 months of age, 17% before 5 months and 8% after 6 months. Concerning CF modalities, 38% suggested Traditional pureed foods spoon feeding following written recommendations (T), 13% suggested a sort of Baby-led weaning (B) while the majority (49%) declared to use both according with family characteristics. Concerning specific advices, 89% declared to suggest meat quantity during the first year of life and 91% suggest to introduce added salt only after 12 months of age. A GPN was followed by 85% of them. NN Pediatricians had a significantly earlier CF starting, an higher use of T modality, meat quantity and added salt advices, and followed more frequently a GNP respect to DR Pediatricians (all p<0, 0001). Conclusions: Our data suggest that the criterion most considered for CF start might be associated with timing, modality and nutritional advices during the first year of life. Pediatricians following the developmental readiness position for CF start could less frequently give to parents adequate nutritional advices for hypertension and obesity prevention. An effort aimed to integrate new CF practices with adequate nutritional recommendations should be strongly encouraged.